Comparative phylogeography of bamboo bats of the genus Tylonycteris (Chiroptera, Vespertilionidae) in Southeast Asia - Tu, Vuong Tan; Csorba, Gábor; Ruedi, Manuel; Furey, Neil M.; Son, Nguyen Truong; Thong, Vu Dinh; Bonillo, Céline; Hassanin, Alexandre (European Journal of Taxonomy, 2017)
In Southeast Asia, bats of the genus Tylonycteris Peters, 1872 have traditionally been classified into two wide-ranging species, T. pachypus (Temminck, 1840) and T. robustula Thomas, 1915. Our comparative phylogeographic analyses based on two mitochondrial and seven nuclear genes, combined with our multivariate morphological analyses, show that these species actually represent cryptic species complexes that share a similar biogeographic history in three major regions, i.e., Sundaland, southern Indochina, and northern Indochina. Our molecular dating estimates suggest that Pleistocene climatic oscillations and sea level changes have repeatedly isolated ancestral populations of Tylonycteris spp. in distant bamboo forest refugia. The analyses indicate, however, that populations of the T. pachypus complex were less affected by forest fragmentation in mainland Southeast Asia than those of the T. robustula complex. Accordingly, we propose several taxonomic changes within the genus Tylonycteris: the species T. fulvida and T. malayana are revalidated, and a new species, T. tonkinensis Tu, Csorba, Ruedi & Hassanin sp. nov., endemic to northern Indochina, is described.